The Effect of the Application of Project-Based Learning Model on Improving Problem-Solving Skills - Wani, Sri; Arismunandar, Arismunandar; Herman, Herman; Mustafa, Mustafa (Pancasila International Journal of Applied Social Science, 2025)
The learning process is a learning activity designed to provide a learning experience that involves mental and physical processes through interaction between children, teachers, learning environments and other learning resources in achieving basic competencies In child development some several aspects and abilities need to be developed, one of which is the cognitive aspect. The development of cognitive aspects is the ability of thinking that a person has to understand and understand something. The cognitive aspect is that children need to develop their abilities according to their respective ages. One of the skills that needs to be developed in children (5-6) years old is problem-solving skills. Problem-solving skills need to be possessed and developed from an early age. Because, in daily life, of course, children will be faced with various problems. So, every child must be able to solve and overcome this problem. This study aims to determine the effect of the application of the project-based learning model on improving problem-solving skills in children aged 5-6 years. The research method used is quantitative research with the Quasi-experimental method, or pseudo-experimentation. The design form used in this study is Nonequivalent Control group Design, which is a design that provides pre-test before treatment, as well as post-test after applying treatment to each group The results of the study show that: 1) An overview of children's problem-solving skills in the control group aged 5-6 years and an overview of children's problem-solving skills in an experimental group aged 5-6 years with the application of a Project-Based Learning Model so that it can be It was concluded that there was an influence of the project method on the problem-solving ability of children aged 5-6 years.